Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Below, explain why we are allowed the"substitute in" x - 3 for y in the top equation.Why is this useful for finding our first solution?x + x = 11y = 1x - 3

Sagot :

You have the following system of equations:

x + y = 11

y = x - 3

it is usefull to replace the expression y = x - 3 into the first equation, because in this way you can solve for x, just as follow:

x + x - 3 = 11 here you replaced y = x - 3. Simplify like terms:

2x - 3 = 11

2x = 11 + 3

2x = 14

x = 14/2

x = 7

Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.